Assessment of Brain Metastasis at Diagnosis in Non–Small-Cell Lung Cancer: A Prospective Observational Study From North India. (2021) - Naresh, Gundu; Malik, Prabhat Singh; Khurana, Sachin; Pushpam, Deepam; Sharma, Vinod; Yadav, Mukesh; Jain, Deepali; Pathy, Sushmita
Abstract : PURPOSE: The incidence of symptomatic brain metastasis at diagnosis in non–small-cell lung cancer (NSCLC) is 5%-10%, and up to 40% develop during the disease course. There is a paucity of data supporting the role of brain imaging at diagnosis in asymptomatic cases particularly from resource-constraint settings. Here, we present our experience of mandatory baseline brain imaging with contrast-enhanced computed tomography (CECT) scans of all patients with NSCLC. MATERIALS AND METHODS: This was a prospective observation study of patients with NSCLC with mandatory baseline brain CECT and a CNS examination. All histology proven patients with NSCLC diagnosed between January 2018 and October 2019 were included irrespective of stage. RESULTS: A total of 496 patients were enrolled. The median age was 57 years (range, 23-84) with majority being males (75%) and smokers (66%). The prevalence of epidermal growth factor receptor mutations and anaplastic lymphoma kinase fusions was 33.4% and 12%, respectively. Brain imaging leads to upstaging in 7% cases. The prevalence of brain metastases was 21% (n = 104), with half being asymptomatic (51%). Factors associated with higher proportion of brain metastasis were young age (⩽ 40 years), adenocarcinoma histology, poor Eastern Cooperative Oncology Group performance status (3 and 4), and high neutrophil-lymphocyte ratio (NLR) (> 2.5). After a median follow-up of 10.8 months (95% CI, 7.33 to 12.73), the median overall survival was 7.46 versus 12.76 months (hazard ratio 0.67; 95% CI, 0.46 to 0.96; P = .03) in patients with and without brain metastases, respectively. On multivariate analyses, high NLR and molecular graded prognostic assessment affected the overall survival significantly. CONCLUSION: In our study, 21% of patients had brain metastasis at diagnosis detected with a mandatory baseline brain imaging with CECT. NLR and molecular graded prognostic assessment are significant predictors of survival in patients with brain metastasis.